GERMINATION OF PORANG (Amorphophalus muelleri) FROM DIFFERENT BULBIL TO VARIOUS PLANTING MEDIA - Nurjannah, Hegar; Umar Harun, Muhammad; Sodikin, Erizal (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2021)
Porang plant is atubers that havevarious benefits. Porang cultivation needs intensive management through cultivation efforts which of course must be supported by the availability of seeds. Therefore, it is necessary to procure porang seeds from vegetative (tubers) and generative (stem bulbil and branch bulbil). This study aims to obtain the best growing media for porang germination from various types of bulbil. The method used in this study was a factorial randomized block design. The way of working in this research is: Preparation of Seedling Media, Preparation of planting material (Bulbil), Seeding, Maintenance (including watering and weeding). The results showed that there was no significant interaction between the planting medium and the type of bulbil, the media had no significant effect on all observed variables, while the bulbil had a significant effect on the percentage of germination growth, stem height, and number of leaves. The best type of bulbil for breeding is stem bulbil which is superior to the variables of plumule emergence time, petiole length, stem height, and number of leaves compared to branch bulbil. Meanwhile, the best growing media in porang nurseries was a mixture of 50% husk charcoal + 50% sawdust on the variables when the plumule appeared, the percentage of germination, petiole length and stem height. The appearance of bulbil from stems on a mixture of 50% husk charcoal + 50% sawdust media, namely the time of emergence of plumules (5.61 days), percentage of sprouting (86.67%), petiole length (8.72 cm), height stems (31.11 cm) and number of leaves (7.72 strands).